Market, interest rate, and exchange rate risk effects on financial stock returns during the financial crisis: AGARCH-M approach - Aloui Mouna; Jarboui Anis (Cogent Economics & Finance, 2016)
Our aim is to investigate the sensitivity of financial sector stock returns to market, interest rate, and exchange rate risk in three financial sectors (financial services, banking, and insurance) in eight countries, including various European, the US, and China economies, over the period 2006-2009 during the financial crisis. The econometric framework is a four-variate GARCH-in-mean model and volatility spillovers. The empirical results show the significant effects (positive and negative, respectively) of the stock market returns, interest rate, and exchange rate volatility of the financial sector during the crisis. Besides, we find, in most cases, significant (positive and negative, respectively) volatility spillovers from market return, interest rate, exchange rate, and interest rate in the financial services and the banking sector both in the European and the US economies during the financial crisis.
Keywords: 330; exchange rate; interest rate; multivariate GARCH; volatility; financial sector stock returns; market linkages in the post-crisis world